2021
DOI: 10.1016/j.isci.2021.102491
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophobic-modified metal-hydroxide nanoflocculants enable one-step removal of multi-contaminants for drinking water production

Abstract: Summary Flocculation is a mainstream technology for the provision of safe drinking water but is limited due to the ineffectiveness of conventional flocculants in removing trace low-molecular-weight emerging contaminants. We described a synthesis strategy for the development of high-performance nanoflocculants (hydrophobic-organic-chain-modified metal hydroxides [HOC-M]), imitating surfactant-assembling nano-micelles, by integration of long hydrophobic chains with traditional inorganic metal (Fe/Al/T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…We also briefly examined some substituted imidazoles to see how substitution on the imidazole would affect the efficiency of sequestration of phenolics from water. We prepared a polyisobutyl-2-phenyl imidazole (11) and the polyisobutylbound tetrasubstituted-imidazole (12). This latter imidazole 12 is a version of a prior imidazole whose imidazolium salts are reported to have remarkable alkaline stability.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also briefly examined some substituted imidazoles to see how substitution on the imidazole would affect the efficiency of sequestration of phenolics from water. We prepared a polyisobutyl-2-phenyl imidazole (11) and the polyisobutylbound tetrasubstituted-imidazole (12). This latter imidazole 12 is a version of a prior imidazole whose imidazolium salts are reported to have remarkable alkaline stability.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Phenolics are often byproducts of other industrial processes. Whatever the source, these phenolics are generally highly toxic water pollutants, and a variety of procedures have been used to affect their removal from water. Common processes for removal of trace phenolics from water include oxidative degradation, biological treatments, flocculation, , liquid/liquid extraction, ,, or, most commonly, adsorption by solid supports. , In some cases, these procedures can be combined.…”
Section: Introductionmentioning
confidence: 99%
“…The flocculant is used to overcome the electrostatic repulsive forces and allow the interfering materials to agglomerate. In addition, a flocculation agent is added to weigh the flakes, because the metal hydroxide sludge formed during flocculation does not sediment well due to its high water content [27]. H 2 O 2 as an oxidizing agent, polyaluminum chloride (PAC) as a flocculant, and polyacrylamide as a flocculant are added to the water through the metering devices.…”
Section: Datamentioning
confidence: 99%
“…metal salts) and flocculants (e.g. chitosan) using hydrophobic organic segments, which has shown promising results in several cases (Du et al, 2018;Liu et al, 2019;Ng et al, 2019;Ren et al, 2017;Yang et al, 2020b;Yang et al, 2021;Zheng and Taylor, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that introducing a moderate amount of hydrophobic segments strengthens pair-wise binding interactions among flocculants, TrOCs and coexisting particles/colloids, which promotes contaminant aggregation (floc formation) and notably improves the removal of trace pharmaceutical (TrPs) (Liu et al, 2019;Ren et al, 2017;Yang et al, 2020b;Yang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%